Getting started in 3D with Maya : create a project from start to finish-model, texture, rig, animate, and render in Maya - Watkins, Adam (William Adam) (Focal Press, 2012)
Deliver professional-level 3D content in no time with this comprehensive guide to 3D animation with Maya. With over 12 years of training experience, plus several award winning students under his belt, author Adam Watkins is the ideal mentor to get you up to speed with 3D in Maya. Using a structured and pragmatic approach Getting Started in 3D with Maya begins with basic theory of fundamental techniques, then builds on this knowledge using practical examples and projects to put your new skills to the test. Prepared so that you can learn in an organic fashion, each chapter builds on the knowledge gained in the previous chapter, showing you all the essentials of 3D in Maya, from modeling and UV layout, to texture creation, rigging animating and rendering. As you go from project to project you'll develop a strong arsenal of skills that combined will form a complete end to end process to creating complete projects in Maya. The accompanying website provides all the tools you need to develop your skills. Project files to accompany the practical examples used throughout the text, so you can work along with the examples. Additional textures and models will give you all the resources you need to start making your own projects in no time at all. --Provides all you need to get started, including a valuable roadmap to the "big picture" of 3D production. Rather than a lengthy description of dialog boxes or option lists, you gain a full understanding of how Maya "thinks" so that you can become effective real-world artists. --Watkins has over twelve years of 3D education experience, having trained hundreds of 3D artists. With multiple award winning students, he knows how people learn 3D, what works and what doesn't, proper pacing, and offers engaging, manageable, yet ambitious tasks. --Create a project from start to finish using all the major components of the 3D process - modeling, UV layout, texture creation, rigging, animation, and rendering - with Maya. --Bonus content for professors! Includes suggested curriculum for 3D based training for semester and year-long sessions, suggested layouts and pacing. How do these chapters fit into a teaching strategy? How long should a class spend on each chapter? All these questions are answered in the included Curriculum Appendices and online resources